PENGARUH VOLUME LIMBAH SERBUK KAYU JATI (TECTONA GRANDIS) TERHADAP DAYA SERAP AIR PADA KOMPOSIT PARTIKEL DENGAN MATRIKS EPOKSI - Desiasni, Rita; Chandra, Rico; Widyawati, Fauzi (Wakil Rektor 3, Direktorat Pengabdian kepada Masyarakat dan Publikasi, Universitas Teknologi Sumbawa, 2021)
The furniture industry is a company that utilizes forest products in the form of wood as the main raw material in the production process. The wood used by the furniture industry in Indonesia reaches 2.6 million m3 per year. The waste generated reached 54.24% of the total production. Sawmill waste generated as much as 1.4 million m3 per year. Based on field observations in several furniture industries in the Sumbawa Region, most industries produce sawdust waste that has not been used optimally, so that sawdust waste accumulates in the soil and decomposes which can trigger environmental pollution and water pollution. Teak sawdust waste has a high cellulose content so it plays an important role as a reinforcement raw material in the manufacture of particle composites. In this study using the hand lay up method of making composite particles by utilizing waste teak sawdust as raw material for reinforcement and epoxy matrix with volume variations of 30:70%, 40:60%, 50:50%, 60:40%, 70:30. %, to obtain quality composite characteristics. Water absorption obtained 14%, each composite specimen has met the standard of SNI 03-2105-2006. The results of physical tests on the water absorption of particleboard composites were the lowest at 0.48% at 30% powder volume with 24 hours immersion due to the wood powder being mixed and bonded evenly by the matrix so as to reduce voids, while the highest yield was 9.41% in 70% volume is due to the matrix not being able to bind evenly, causing voids to occur. It can be concluded that the increasing volume of powder and the length of time of immersion, the greater the percentage value of water absorption produced.